Iliac bone biopsy and analysis: A clinical, translational, and cadaveric review - Jay J. Byrd; Ethan L. Snow; Travis L. McCumber (Translational Research in Anatomy, 2023)
Introduction: The evolution of bone excision and analysis led to the utilization of the iliac crest and ala in the 1950s. Scientific interest in metabolic bone disorders in the 1960s and 1970s stimulated the development of new surgical protocols for obtaining large diameter iliac crest biopsies. Today, these clinical and translational protocols are used to study a wide spectrum of bone disorders. The authors of this review noted that the utilization of cadaveric iliac bone biopsy to supplement the analysis of the bone disorder spectrum had yet to be summarized. Considering the limitations of clinical and translational application of iliac bone biopsy analysis and the lack of a cadaveric iliac bone biopsy review within the primary literature, the following article presents a history of bone excision, the foundation of clinical and translational application of iliac bone biopsy analysis, and a systematic literature review of published cadaveric iliac bone biopsy analysis. Methods: A systematic literature search of keywords, (cadaver) AND ((iliac) OR ((ilial)) OR (ilium)) AND (bone biopsy), was conducted using the PubMed NCBI database. Subsequently, the 109 results were individually analyzed. Results: Eighteen articles were identified as studies utilizing cadaveric iliac bone biopsy to analyze a spectrum of bone disorders. The remaining articles were unrelated to the motivation and objective of this review. Discussion: While analysis of cadaveric bone integrity has produced mixed results and the utilization of cadaveric iliac bone biopsy analysis is not without its own limitations, studies have been reported to span a wide variety of applications. Categorically, these studies include comparisons of anatomical location, age and/or sex differences, metabolic or structural bone disorders, reconstruction, geographic or environmental comparisons, and new techniques and analysis. Conclusions: Considering the benefits and challenges of iliac bone biopsy, a comprehensive approach including clinical, translational, and cadaveric iliac bone biopsy analysis is necessary to maximize the scientific understanding of a spectrum of bone disorders while minimizing the limitations of each methodology.